The Effect of Workplace Incivility on Psychological Well Being in Health Nurses With Emotional Exhaustion as a Mediator Variable - Tamara Dwi Astari; Rahmi Lubis; Patisina Patisina (Universitas Ahmad Dahlan, 2024)
Nurses are health services provider professionals. The work demands have detrimental effects on nurses' physical and mental health, which risk their psychological well-being. The psychologically well nurses will provide high-quality care with implications for patient recovery. Interpersonal relationships with co-workers and superiors influence nurses' well-being. Poor treatment in the work environment (workplace incivility) can cause nurses to be psychologically unwell. However, we do not yet know how workplace incivility affects psychological well-being. This study aims to examine the effect of workplace incivility on nurses' psychological well-being through the mediation of emotional exhaustion. This explanatory quantitative study involved 270 health nurses at Hospital X Medan. We analyzed data using the Structural Equation Model (SEM) with the Smart-PLS program. Results indicated that emotional exhaustion mediated the effect of workplace incivility on nurses' psychological well-being. This study contributes to nurses' well-being intervention, which is influenced by workplace incivility and mediated by emotional exhaustion.